Measurement properties of multidimensional patient‐reported outcome measures in neurodisability: a systematic review of evaluation studies - Janssens, A; Rogers, M; Gumm, R; Jenkinson, C; Tennant, A; Logan, S; Morris, C (Wiley, 2015)
Aim: To identify and appraise the quality of studies that primarily assessed the measurement properties of English language versions of multidimensional patient‐reported outcome measures (PROMs) when evaluated with children with neurodisability, and to summarize this evidence. Method: MEDLINE, Embase, PsycINFO, CINAHL, AMED, and the National Health Service Economic Evaluation Database were searched. The methodological quality of the papers was assessed using the COnsensus‐based Standards for selection of health Measurement INstruments checklist. Evidence of content validity, construct validity, internal consistency, test–retest reliability, proxy reliability, responsiveness, and precision was extracted and judged against standardized reference criteria. Results: We identified 48 studies of mostly fair to good methodological quality: 37 papers for seven generic PROMs (CHIP, CHQ, CQoL, KIDSCREEN, PedsQL, SLSS, and YQOL), seven papers for two chronic–generic PROMs (DISABKIDS and Neuro‐QOL), and four papers for three preference‐based measures (HUI, EQ‐5D‐Y, and CHSCS‐PS). Interpretation: On the basis of this appraisal, the DISABKIDS appears to have more supportive evidence in samples of children with neurodisability. The overall lack of evidence for responsiveness and measurement error is a concern when using these instruments to measure change, or to interpret the findings of studies in which these PROMs have been used to assess change.